Perceptions of instructors and students about gender equality: innovation in the English as a foreign language speaking practice - Villafuerte, Jhonny; Gavilanes Coppiano, María José (Technium Education and Humanities, 2023)
The objective of this work is to contribute to the humanization of linguistic practices in the English language class from the perspective of gender equity in the training process of foreign language teachers. The results allow us to determine moderate advances in the gender equity approach from the English classroom. It proposes routes to enhance language practices from a gender equity perspective as an action that contributes to the profile of the teacher in training and sustainable development in educational communities that can be adjusted according to the educational policies of various nations.